Isolation and Extraction of Medicinally Useful Dye from the Heartwood of Caesalpinill sappan Linn. using Different Solvents. - GULERIA, B.S.; MANAV, A.K.; INDRAYAN, A.K. (Asian Journal of Chemistry, 2010)
Heartwood of Caesalpinia sappan, an indigenous tree, is a source of medicinally useful dye. It serves the dual purpose-colouring matter and treatment of certain ailments as well. Using the various solvents for extraction, viz., water, methanol, ethanol and aqueous caustic soda, the dark brown solid (aqueous solution orange), dark orange-red viscous liquid, reddish brown semi-solid (orange-red solution), and dark brown semisolid (red-violet solution) respectively are obtained, expected to have varied medicinal value as well.